Tetradentate N2O2 Chelated Palladium(II) Complexes: Synthesis, Characterization, and Catalytic Activity towards Mizoroki-Heck Reaction of Aryl Bromides - Siti Kamilah Che Soh; Mustaffa Shamsuddin (Journal of Chemistry)
Four air and moisture-stable palladium(II)-Schiff base complexes, N,N′-bis(α-methylsalicylidene)propane-1,3-diamine palladium(II) (2a), N,N′-bis(4-methyl-α-methylsalicylidene)propane-1,3-diamine palladium(II) (2b), N,N′-bis(3,5-di-tert-butylsalicylidene)propane-1,3-diamine palladium(II) (2c), and N,N′-bis(4-methoxy-salicylidene)propane-1,3-diamine palladium(II) (2d), have been successfully synthesised and characterised by CHN elemental analyses and conventional spectroscopic methods. These complexes were investigated as catalysts in the phosphine-free Mizoroki-Heck cross-coupling reactions of aryl bromides with methyl acrylate.